2022
DOI: 10.37290/ijpp2641-7197.17:33-41
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Modulation of Gut Microbiota by Personalized Probiotics

Abstract: The current market of probiotic supplements is significantly growing although the quality and effectiveness of the commonly sold products are variable. Parameters such as the composition of each individual microbiota, strain specificity, production procedures, or storage can influence the potential positive outcome of probiotic supplements on consumers. The aim of this study was to determine changes of selected markers within the microbiota after 3 months treatment by the personalized probiotic supplement. Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Results showed that the probiotic supplementation improved stool frequency in both cases-constipation and also diarrhea. The study confirmed the significance of a personalized approach in probiotic supplementation [50]. Of course, further data and studies are needed to demonstrate the effectiveness of a personalized approach in the clinical field.…”
Section: Personalized and Targeted Microbiota Modulation And Its Pote...supporting
confidence: 64%
“…Results showed that the probiotic supplementation improved stool frequency in both cases-constipation and also diarrhea. The study confirmed the significance of a personalized approach in probiotic supplementation [50]. Of course, further data and studies are needed to demonstrate the effectiveness of a personalized approach in the clinical field.…”
Section: Personalized and Targeted Microbiota Modulation And Its Pote...supporting
confidence: 64%